The value of adult orthodontics: Do the public's willingness-to-pay values reflect the profession's?. (June 2022) - Edwards, Kathryn; Rae, Jennifer; Rolland, Sarah; Vernazza, Christopher R.
Objective: To explore how the public and dental professionals would value an orthodontic service for adults by eliciting their willingness-to-pay (WTP), a standardised health economics technique which quantifies 'strength of preference' in monetary terms. Despite increasing demand, adults in the UK are only eligible for NHS orthodontic treatment if there is severe dental health or complex multidisciplinary need. Orthodontic services are provided to children aged under 18 years who are eligible by their Index of Orthodontic Treatment Need (IOTN) score. Consequently, many adults who may have a need for treatment as determined by IOTN are unable to access this service. Design: Cross-sectional survey. Setting: General dental practices in North East England and national specialists approached through the British Orthodontic Society (BOS). Participants: Public participants were recruited from general dental practices. Dentists were recruited from local dental lists and members of the BOS. Methods: Participants were asked if they would be willing to pay to see an orthodontic service extended to all adults in England with a qualifying IOTN. Clinical photographs of three malocclusions were presented and maximum WTP in additional tax per household per year was elicited using shuffled payment cards. Results: A total of 205 dentists and 206 public participants were recruited. Pairwise tests showed a statistically significant difference in WTP between the public and professionals for all malocclusions, with the public giving higher valuations. In both groups, the Class III scenario elicited a higher WTP than the class I or II malocclusion. However, when all other factors were controlled for using a regression analysis, the group (public or profession) and the other variables did not significantly influence WTP. Conclusion: The public and professionals were willing to pay for an adult orthodontic service. Due to this variability and unpredictability the allocation of healthcare resources will remain contentious.